Reflection of a longitudinal wave from a notch in the rod immersed into a viscous fluid - Ilgamov, Marat Aksanovich; Khakimov, Akim Gayfullinovich (Computational Continuum Mechanics, 2010)
The reflection of a longitudinal damping traveling wave from a cross notch and its passage along the rod immersed into a viscous fluid have been investigated. The simplest model capable of describing the stress-strain state in the notch zone is used. The dependence of the solution on the notch parameters and the damping characteristics of the rod material and surrounding fluid has been obtained. The solution of the inverse problem enables us to find the coordinate of the notch and its depth and length parameters using the data for the incident and reflected waves obtained at the point of observation.
Keywords: rod; longitudinal wave; damping; primal and inverse problems